Staged reality in cinema: Semantic context - Barnych, Mykhailo; Balaban, Oleksandr; Kotlyar, Svitlana; Saminina, Hanna; Venher, Olena (Linguistics and Culture Review, 2021)
The relevance of this subject is related to the development of information technology and new media, which has allowed wide access to cinema as a visual activity. The information media space is increasingly connected to human existence, and the demand for intangible goods and services inherent in post-industrial society is causing increasing demands for intellectual products outside the science and production industry. In this context, the purpose of the study is to identify the plane of the significance of the staged reality of cinema as a dominant form of synthetic art, the attitude between artistic and nonartistic features of staged reality on the example of fiction and documentary cinema, and to outline the transformation of the structure of film reality as a constructor and medium. The principal approaches to the study were structural and hermeneutic approaches to structural analysis in terms of the semiotics of culture of cinema reality sign space and the use of interpretive practices on textual objects. At the level of basic structures, the interaction between meaning and signification and the transformation of the semantic matrix of cinema as a form of art is discussed, at the level of discourse the individual film picture.